DIFFERENCES OF PEAK EXPIRATION FLOW RATE (PEFR) BETWEEN BRISK WALKING AND HIGH INTENSITY INTERVAL TRAINING (HIIT) IN YOUNG ADULTS - Vania Nazhara Fitriana; Yosef Purwoko; Sumardi Widodo; Tanjung Ayu Sumekar (Faculty of Medicine, Diponegoro University, Semarang, Indonesia, 2020)
Background : Sedentary lifestyle makes people having less physical activities that may lead to the reduce lung function. Peak expiratory flow rate (PEFR) was used to measure lung function. High Intensity Interval Training (HIIT) is a high-intensity aerobic exercise, while brisk walking is an moderate-intensity aerobic exercise. The aim of this research is to determine the difference of PEFR between HIIT and brisk walking, that could depict lung function. Method : This research used quasi experimental with pre-test and post-test comparison group design. The samples were medical students at Diponegoro University, who had inclusion criteria and did not have exclusion criteria. This research used samples of 3 groups that contained of control group, HIIT, and brisk walking with 14 people in each group. Groups of HIIT and brisk walking got 3 times of intervention in each week, for 6 weeks. Measurement of PEFR was using Miniwright Peak Flow Meter. The normality of numerical scaled data was tested by using Saphiro-Wilk method, to find abnormal data that was tested by using Mann Whitney Method. Results : The average post-test of PEFR in HIIT was (397.14±33.738), while in brisk walking was (370.14±34.851), and in the control group was (327.78±29.271). The increase in PEFR between the HIIT and the brisk walking group after statistical testing was p = 0.000 (p <0.005), which shows a significant difference. Conclusion: There is a significant difference in the PEFR between HIIT group and brisk walk in early adults that could describe a person's lung function.Keywords : Lung Function, PEFR, HIIT, Brisk walking.